KEBEBASAN PERS DI INDONESIA PADA ERA REFORMASI DAN EKONOMI POLITIK MEDIA - Martono, Joko (Jurnal Insani, 2014)
Freedom of the press in Indonesia is guaranteed in the Act No. 40 of 1999. Variety article that relates to freedom of the press be substantially embodied the meaning is universal and tend to be liberal. For entrepreneurs, the existence of media institutions is seen as a land of business will bring profits. Therefore as the implications on the basis of the application of those concepts, information has become as valuable commodities exchange. The product is packaged in such a way the media become interchangeable merchandise and have economic value. A new outbreak of mass media companies marked increases the television industry in Indonesia has shown that "information business" which is done through a political economic strategy has been growing rapidly. The impact of the industrialization was plentiful. Public sphere (public sphere) is supposed to belong together or put together is now likely to become the monopoly of the media. Conflict of interest between managers of the media, the authorities and the audience is still found. In other words, there has been a difference in relations, especially relations between the interests of the market and social interests.